UJI AKTIVITAS EKSTRAK ETANOL 96% BIJI SRIKAYA (Annona squamosa L.) SEBAGAI ANTIDIARE YANG DISEBABKAN OLEH BAKTERI Shigella dysenteriae DENGAN METODE DIFUSI CAKRAM - Leonov Rianto; Indri Astuti Handayani; Annisa Septiyani (Jurnal Ilmiah Manuntung, 2015)
This research aims to find out how to extract ethanol 96% seed custard apples as Antidiarrhoeal that is caused by bacteria Shigella dysenteriae with different concentrations and compare with chloramphenicol. In addition, also to find out whether their respective inhibitory power of concentration of ethanol 96% seed extract custard apples have a difference in meaning. Research done by experimental methods, was carried out in the laboratory of pharmaceutical Academy IKIFA. Testing was done using the diffusion disc method. The concentration of ethanol 96% seed extract custard apples are used i.e. 15%, 30%, 45%, 60%, and 75%. As positive controls used chloramphenicol 30 µg/ml and NaCl 0.9% as the negative control. Each test is carried out as many as eight repetitions. The results showed an average diameter drag power which formed on the test solution with a concentration of 15%, 30%, 45%, 60% and 75% respectively of 6,887 mm, 11,49 mm, 8,144 mm, 7,694 mm, 7,150 mm, whereas for chloramphenicol for 40,31 mm. Based on the results of the statistical tests there are meaningful differences between concentrations showed a meaningful difference between the concentration of 15% and 30%, 15% and 60% and 15% and 75%. Conclusion of this research is at a concentration of 15%, 96% ethanol extract of seeds of custard apples have been able to inhibit the growth of bacteria, Shigella dysenteriae